Inflammation biomarkers and delirium in critically ill patients - Ritter, Cristiane (BioMed Central, 2014)
INTRODUCTION: Delirium is a common occurrence in critically ill patients and is associated with an increase in morbidity and mortality. Septic patients with delirium may differ from a general critically ill population. The aim of this investigation was to study the relationship between systemic inflammation and the development of delirium in septic and non-septic critically ill patients. METHODS: We performed a prospective cohort study in a 20-bed mixed intensive care unit (ICU) including 78 (delirium = 31; non-delirium = 47) consecutive patients admitted for more than 24 hours. At enrollment, patients were allocated to septic or non-septic groups according to internationally agreed criteria. Delirium was diagnosed using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) during the first 72 hours of ICU admission. Blood samples were collected within 12 hours of enrollment for determination of tumor necrosis factor (TNF)-α, soluble TNF Receptor (STNFR)-1 and -2, interleukin (IL)-1β, IL-6, IL-10 and adiponectin. RESULTS: Out of all analyzed biomarkers, only STNFR1 (P = 0.003), STNFR2 (P = 0.005), adiponectin (P = 0.005) and IL-1β (P < 0.001) levels were higher in delirium patients. Adjusting for sepsis and sedation, these biomarkers were also independently associated with delirium occurrence. However, none of them were significant influenced by sepsis. CONCLUSIONS: STNFR1, STNFR2, adiponectin and IL-1β were associated with delirium. Sepsis did not modify the relationship between the biomarkers and delirium occurrence.